Characteristics of the perception of the nursing profession by Polish students of medicine - Zarzycka, Danuta; Marcinowicz, Ludmiła; Foley, Mary; Ślusarska, Barbara; Windak, Adam; Cuber, Tomasz; Buczkowski, Krzysztof; Dobrowolska, Beata (Polish Journal of Public Health, 2012)
Introduction. The extent of mutual collaboration between physicians and nurses can be influenced by ascribed social roles and cultural standards. Aim. The objective of the study is the presentation of medical students’ opinions concerning the perception of the nursing profession, and an attempt to determine the factors conditioning this perception. Material and methods. The studies of a descriptiveexplanatory character were conducted with the use of the Professional Nursing Image Survey, and covered a group of 900 medical students from three universities in Poland. The results were subject to mathematical analysis with the use of basic software. Results. The statistical analysis of the results of studies confirm previously observed determinants of the perception of the professional role of a nurse by physicians, i.e. gender and, to a smaller degree, student’s period of training (year of study). Conclusion. Medical students in Poland believe that the Polish nurses’ ways of therapeutic performance restrict their way to more independent practice. Analysis of the opinion of medical students on the nursing profession can contribute to the greater autonomy of professional nurses. Practice implications. The perception of nurses’ professional role may be determined by social and cultural factors but also through cooperation in education of medical and nursing students.